What Is the Relationship Between Sensory Attributes Identified Using CATA (Check-All-That-Apply) Questionnaire and Consumer Acceptance of Cookies Using Plant-Based Oils? - Juyoun Lee; Seyoung Ju (Foods)
The purpose of this study was to investigate sensory attributes identified using a CATA questionnaire and consumer acceptance of cookies using plant-based oils and to determine which sensory attributes influence and improve purchase intention of cookies using plant-based oils. Frequency analysis, one-way analysis of variance, correspondence analysis, Pearson correlation analysis, and multiple factor analysis were used for statistical evaluation. Six cookie samples, five with types of vegetable oil (canola, brown rice, coconut, soybean, olive) and one with butter, were evaluated by 112 consumers. Of the 28 sensory attributes, the 11 sensory terms of milk, savory, sweet aroma/odor, sweet, roasted grain, milk taste/flavor, hardness, “crispy”, “stuffy”, roughness, and “crumble” were significantly different among samples (p < 0.001). In the consumer acceptance and purchase intention tests, participants evaluated 12 attributes, namely, overall liking, appearance, color, aroma/smell, overall taste, savory flavor, flavor, sweet taste, aftertaste, texture, “smooth”, “crispy”, “try again”, recommendations, and familiarity, on a 9-point structured hedonic scale. All attributes except “smooth” were significantly different among the six cookie samples tested (p < 0.001). Samples with coconut oil and butter had the highest consumer acceptance. In particular, in a correspondence analysis, the samples with butter and coconut oil positioned in the positive direction (+) of Dimension (Component) 1 were closely related with mouthfeel, sweet aroma, sweet taste, “crispy”, “try again”, recommendation, familiarity, and overall liking. Our results suggest that cookies with coconut oil could be a substitute for animal-fat-based cookies with butter. We hope that our research will provide fundamental data for the development of vegan bakery products that meet the needs of consumers and food companies.